Analisis Kebijakan Kawasan Gunung Batur di Desa Batur Tengah, Kecamatan Kintamani, Kabupaten Bangli menjadi Global Geopark Network (GGN) - I Made Nata Hari Wisnu Wardana; Anak Agung Ayu Dewi Larantika (Universitas Warmadewa, 2022)
The background of this research is considering that the advantage of having a geopark for Kintamani tourist attraction, namely the promotion that continues to be carried out by UNESCO. In addition, it can increase the value of the site, create jobs, and encourage sustainable socio-economic development. However, until now there have not been many positive changes in the Kintamani tourism industry. The formulation of the research problem is 1). Why is the policy of the Mount Batur Area in Batur Tengah Village, Kintamani District, Bangli Regency as a Global Geopark Network (GGN) not effective? 2). What are the factors that hinder the policy of the Mount Batur Area in Batur Tengah Village, Kintamani District, Bangli Regency as a Global Geopark Network (GGN)?. The theory used in this study is the theory of William N. Dunn Retrospective Model in which the researcher analyzes the impacts that may arise 'after' the policy of the Mount Batur Area into the Global Geopark Network (GGN). This study uses descriptive qualitative analysis with data collection through observation, interviews, and documentation. The results of the study stated that the policy of the Mount Batur area in Batur Tengah Village, Kintamani District, Bangli Regency to become a Global Geopark Network (GGN) has an impact on socio-cultural life, and the economy. The factors that become obstacles in the Mount Batur area as a Global Geopark Network (GGN) are 1). Contents of policies, 2). Information, 3). Support, and 4). Potential distribution.